Optimalisasi Pemungutan Retribusi Pelayanan Parkir Di Tepi Jalan Umum Oleh Dinas Perhubungan Kota Ternate - Nisma Ode; Rusman Soleman; Hartaty Hadady (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
This study aims to find out how the implementation of the collection of parking fees on public roads by the Department of Transportation of the City of Ternate, as well as knowing and analyzing the inhibiting factors for optimizing parking fees on public roads, and knowing what efforts are being made to overcome the inhibiting factors for optimizing parking fees. on the edge of a public road by the Department of Transportation of the City of Ternate. This study uses a qualitative-descriptive research method. Data collection techniques were carried out by participatory observation, in-depth interviews, and documentation. The results showed that the optimization of the collection of parking service fees on the edge of public roads by the Department of Transportation of the City of Ternate encountered obstacles in its implementation, namely: different revenue targets, lack of human resources for officers, manual collection system, limited infrastructure facilities, and regulations that have not adapted to developments. Based on this, it can be said that the levy collection process has been carried out, but has not run optimally as it should.